Assisted Performance in Different Task Types of Online Discussion - Ab. Jalil, Habibah; McFarlane, Angela; Ismail, Ismi Arif; Steven, Eric Krauss (European Journals, Inc., 2008)
Screen technology enables people to read, write, obtain information and communicate through text manipulation in a wider open space. The role of screen in replacing paper handouts has an impact on human literacy (Kress, 2003) especially for education and communication purposes. In the context of online teaching and learning like e-learning, teachers are no longer viewed as the main source of knowledge. Likewise, students are no longer seen as individuals who only absorb what is taught. Through discussion, students mutually learn from each other (peer-learning). This study investigates ‘teaching’ behaviour evidenced in activities involving a group of university students using the Learning Management System (LMS) as a tool for discussion. From a socio-cultural perspective, this study will scrutinize the online teaching and learning processes and highlight the significance of the ‘mediation’ element in life, particularly in the field of lifelong learning. Socio-cultural ideas, particularly by Tharp and Gallimore’s (1988)suggest four-stage model of progression through the Zone of Proximal Development (ZPD)to frame our understanding of the nature of assisted performance provided by the participants in their interaction. This model provides the framework for understanding the online learning styles of university students.